1999
DOI: 10.1136/vr.144.21.581
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic treatment of dairy cows and its effect on milk production

Abstract: The results of more than 80 experiments on gastrointestinal parasitism and the impact of anthelmintic treatment on milk production in dairy cattle were reviewed. Abattoir surveys of culled dairy cows, faecal egg counts in milking cows, and serological tests and worm counts in cull cows in milk production studies were collated to assess the level of parasitism in dairy herds. The studies were divided into four general categories: induced infections in previously uninfected cattle; naturally infected cattle trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(72 citation statements)
references
References 55 publications
8
61
0
3
Order By: Relevance
“…In dairy cows many studies with controversial results have been carried out to assess whether anthelmintic treatment have a beneficial effect. The review of Gross et al (1999) showed that in general there was an economical profit from treatments, with a median increase of 0.63 kg of milk per cow per day over that of untreated cows. On the other hand, there are few corresponding references on dairy sheep, as the sheep industry was primarily focused on wool or meat, in which milk production is only considered a maternal aptitude or capacity to rear their lambs.…”
Section: Discussionmentioning
confidence: 99%
“…In dairy cows many studies with controversial results have been carried out to assess whether anthelmintic treatment have a beneficial effect. The review of Gross et al (1999) showed that in general there was an economical profit from treatments, with a median increase of 0.63 kg of milk per cow per day over that of untreated cows. On the other hand, there are few corresponding references on dairy sheep, as the sheep industry was primarily focused on wool or meat, in which milk production is only considered a maternal aptitude or capacity to rear their lambs.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal egg counts have traditionally been utilized to identify and quantify infections, however, this test is plagued with false negatives, high variability between consecutive tests (low repeatability), and overall underestimation of the level of infection (Gross et al, 1999;Agneessens et al, 2000;Borgsteede et al, 2000;Eysker and Ploeger, 2000). Serum pepsinogen tests have had some success with quantifying levels of parasitism in first-season grazers, but were less reliable when used to quantify infections in adult cattle (Gross et al, 1999;Agneessens et al, 2000;Borgsteede et al, 2000). Unfortunately, the accuracy of the pepsinogen test depends on the current life cycle stages of the nematodes in the host (Berghen et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested from both experimental studies and epidemiological surveys in dairy cattle that animals from high producing herds are more infected than others [44] and that, both on a herd and on an individual basis, high producing cows benefit more from anthelmintic treatments than low producing ones [3,25,55].…”
Section: Identification Of Less Resistant/resilient Animals Related Tmentioning
confidence: 99%